2011
DOI: 10.4314/eamj.v87i6.63078
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of post dural puncture headache following Caesarean section under spinal anaesthesia at the Aga Khan University Hospital, Nairobi

Abstract: Background: Post dural puncture headache can be a debilitating complication of subarachnoid anaesthesia for a new mother. Successful management of post dural puncture headache requires adherence to clear policies and protocols with close follow up of patients by an experienced obstetric anaesthetist. Objectives: To examine the cumulative incidence and severity of post dural puncture headache in obstetric patients who consented for spinal anaesthesia for Caesarean section. Design: Prospective cohort study. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
15
2
Order By: Relevance
“…Cutting needles (Quincke needles) are associated with a higher incidence of PDPH compared to blunt or pencil-point needles (Sprotte and Whitacre needles). Schmittner et al [31] and Gisore et al [32] confirmed the significantly lower incidence of PDPH with pencil-point needles compared to Quincke cutting needles in similar studies (1.7% vs. 6.6%, P = 0.02 and 4.5% vs. 24.2%, P = 0.042). A modification of the Quincke (Atraucan) needle is also available, with a cutting point and a double bevel to cut a small dural hole and then dilate it.…”
Section: Risk Factorsmentioning
confidence: 73%
“…Cutting needles (Quincke needles) are associated with a higher incidence of PDPH compared to blunt or pencil-point needles (Sprotte and Whitacre needles). Schmittner et al [31] and Gisore et al [32] confirmed the significantly lower incidence of PDPH with pencil-point needles compared to Quincke cutting needles in similar studies (1.7% vs. 6.6%, P = 0.02 and 4.5% vs. 24.2%, P = 0.042). A modification of the Quincke (Atraucan) needle is also available, with a cutting point and a double bevel to cut a small dural hole and then dilate it.…”
Section: Risk Factorsmentioning
confidence: 73%
“…17 Schmittner et al and Gisore et al confirmed this same finding in their studies in which the use of the Quincke cutting needle was associated with a higher incidence of PDPH compared with the pencil-point needle (6.6% vs 1.7%; p = 0.02 and 24.2% vs 4.5%; p = 0.042). 18,19 Several studies have affirmed that the bigger the bore size of a spinal needle, the larger the dural tear and the greater the incidence of PDPH. 1,2,5,20 However, Schmittner et al failed to demonstrate a significant difference in the incidence of PDPH between 29 G and 25 G Quincke needles (p = 0.6870), 18 suggesting that at very small bore sizes the needle design may be a more important predictor of PDPH than bore size.…”
Section: Pathogenesismentioning
confidence: 99%
“…After assessing full texts of 26 studies, we excluded 9 trials for a variety of reasons. Four studies were not RCTs . One study was retrospective .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were not RCTs. [30][31][32][33] One study was retrospective. 34 One study was a review article.…”
Section: Excluded Studiesmentioning
confidence: 99%